Normal coronary angiograms: financial victory from the brink of clinical defeat? - Keavney, B. (1996)
OBJECTIVE: To examine the hypothesis that, in patients undergoing coronary angiography for suspected ischaemic heart disease, a normal angiographic result is associated with a fall in consumption of health care resources following the angiogram. DESIGN: Retrospective cost-benefit analysis comparing the 12 month periods before and after coronary angiography. SETTING: Tertiary cardiac referral centre. SUBJECTS: 69 consecutive patients investigated in the financial year 1991-92 whose angiograms were normal. MAIN OUTCOME MEASURES: Drug and hospital admission costs in the 12 month periods before and after angiography; urgent and elective consultations with general practitioner in that time. RESULTS: The mean cost of care per patient in the year before investigation was 656.89 pounds. A highly significant fall in all indices of resource consumption was observed in the year following investigation, the mean resulting difference in the cost of care being 35.15 pounds per month. The cost of coronary angiography would, if this fall were maintained, be recouped in a mean time of 18 months. CONCLUSIONS: Patients suspected on clinical grounds to have coronary atherosclerosis who are found at angiography to have normal coronary arteries are heavy consumers of health care resources. Early investigation for these patients is safe and has beneficial resource consequences in the medium term.